Analisis Faktor-Faktor yang Mempengaruhi Penerimaan Pajak Daerah di Kabupaten Kotawaringin Timur - Aurelia Evrida, Agatha; Saleh, Muhammad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
The implementation of autonomy, which focuses on regencies/municipalities, is anticipated to be self-sufficient in terms of managing their own revenue and spending. It is intended to optimize regional income in this scenario by integrating PAD, one of which is obtained from Regional Taxes. The purpose of this study is to determine the extent to which population and per capita GRDP have an impact on local tax revenues in East Kotawaringin Regency. The Central Statistics Agency (BPS) of East Kotawaringin Regency was the source of the data used in this study. Multiple Linear Regression Model (OLS), Statistical Tests (t test and f test), and the Classical Assumption Test are all used in this study. According to the findings of this study, the population variable has a positive but non-significant influence on local tax revenue in East Kotawaringin district, whereas Per capita GRDP has a positive and significant effect on local tax revenue in East Kotawaringin.